Calcitonin gene-related peptide is a key neurotransmitter in the neuro-immune axis - Assas, Bakri M.; Pennock, Joanne I.; Miyan, Jaleel A. (Frontiers in Neuroscience, 2014)
The question of how the neural and immune systems interact in host defence is important, integrating a system that senses the whole body with one that protects. Understanding the mechanisms and routes of control could produce novel and powerful ways of promoting and enhancing normal functions as well as preventing or treating abnormal functions. Fragmentation of biological research into specialities has resulted in some failures in recognising and understanding interactions across different systems and this is most striking across immunology, haematology and neuroscience. This reductionist approach does not allow understanding of the in vivo orchestrated response generated through integration of all systems. However, many factors make the understanding of multisystem cross-talk in response to a threat difficult, for instance the nervous and immune systems share communication molecules and receptors for a wide range of physiological signals. But, it is clear that physical, hard-wired connections exist between the two systems, with the key link involving sensory, unmyelinated nerve fibres (c fibres) containing the neuropeptide calcitonin gene-related peptide (CGRP), and modified macrophages, mast cells and other immune and host defence cells in various locations throughout the body. In this review we will therefore focus on the induction of CGRP and its key role in the neuroimmune axis.